Protein binding characteristics and pharmacokinetics of ceftriaxone in intensive care unit patients. (11th June 2015) - Schleibinger, Michael; Steinbach, Cathérine L.; Töpper, Christoph; Kratzer, Alexander; Liebchen, Uwe; Kees, Frieder; Salzberger, Bernd; Kees, Martin G.
<x xml:space="preserve">Abstract</x> Aims The aim of the present study was to assess the pharmacokinetics of total and unbound ceftriaxone in intensive care unit (ICU) patients and its protein binding characteristics. Methods Twenty patients (m/f 15/5, age 25–86 years, body weight 60–121 kg, APACHE II 7–40, estimated glomerular filtration rate 19–157 ml min–1, albumin 11.7–30.1 g l–1, total bilirubin <0.1–36.1 mg dl–1) treated with intravenous ceftriaxone were recruited from two ICUs. Timed plasma samples were obtained using an opportunistic study protocol. Ceftriaxone concentrations were determined by high‐performance liquid chromatography; unbound concentrations were determined after ultrafiltration using a new method which maintains physiological pH and temperature. The pharmacokinetics was described by a one‐compartment model, the protein‐binding characteristics by Michaelis–Menten kinetics. Results For total drug, the volume of distribution was 20.2 l (median; interquartile range 15.6–24.5 l), the half‐life 14.5 h (10.0–25.5 h) and the clearance 0.96 l h–1 (0.55–1.28 l h–1). The clearance of unbound drug was 1.91 l h–1 (1.46–6.20 l h–1) and linearly correlated with estimated glomerular filtration rate (slope 0.85, y‐intercept 0.24 l h–1, r2 = 0.70). The unbound fraction was higher in ICU patients (33.0%; 20.2–44.5%) than reported in healthy volunteers, particularly when renal impairment or severe hyperbilirubinaemia was present. In all patients, unbound concentrations during treatment with ceftriaxone 2 g once daily remained above the EUCAST susceptibility breakpoint (≤1 mg l–1) throughout the whole dosing interval. Conclusions Protein binding of ceftriaxone is reduced and variable in ICU patients due to hypoalbuminaemia, but also to altered binding characteristics. Despite these changes, the pharmacokinetics of unbound ceftriaxone is governed by renal function. For patients with normal or reduced renal function, standard doses are sufficient.